1992
DOI: 10.1002/pro.5560010713
|View full text |Cite
|
Sign up to set email alerts
|

Role of interchain α‐helical hydrophobic interactions in Ca2+ affinity, formation, and stability of a two‐site domain in troponin C

Abstract: We have previously shown that a 34-residue synthetic peptide representing the calcium-binding site I11 of troponin C formed a symmetric two-site dimer consisting of two helix-loop-helix motifs arranged in a head-to-tail fashion (Shaw, G.S., Hodges, R.S., & Sykes, B.D., 1990, Science249, 280-283). In this study the hydrophobicities of the a-helices were altered by replacing L-98 and F-102 in the N-terminal region and/or 1-121 and L-122 in the C-terminal region with alanine residues. Our results showed that subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…The free energy surfaces for the topology based models of binding of Arc-repressor, 67,68 troponin C site III, 69 FIS dimer, 70 and Trp-repressor 71 are shown in Figure 2 as a function of Q Total and the separation distance between the two chains. For Arc-repressor, troponin C site III, and FIS dimer, two states exist at equilibrium: unfolded monomers and folded dimers, i.e.…”
Section: Coupled Folding-binding Reactionsmentioning
confidence: 99%
“…The free energy surfaces for the topology based models of binding of Arc-repressor, 67,68 troponin C site III, 69 FIS dimer, 70 and Trp-repressor 71 are shown in Figure 2 as a function of Q Total and the separation distance between the two chains. For Arc-repressor, troponin C site III, and FIS dimer, two states exist at equilibrium: unfolded monomers and folded dimers, i.e.…”
Section: Coupled Folding-binding Reactionsmentioning
confidence: 99%
“…These and other (107, 118) studies have clearly indicated that dimerization of single HLH structures control Ca 2ϩ affinity and that even the homodimers bind two calcium ions with positive cooperativity. Clearly, the detailed hydrophobic interactions in the interface between calcium binding sites stabilize the domain and control Ca 2ϩ affinity (119).…”
Section: Helix-loop-helix Ca 2؉ Binding Motifsmentioning
confidence: 99%
“…Single-site model peptides have been used to explore calcium a$nity in the EF-hand site using such techniques as circular dichroism (Akerfeldt et al, 1996;Monera et al, 1992;Procyshyn & Reid, 1994a, b;Reid, 1987aReid, , 1990Reid et al, 1980Reid et al, , 1981Reid & Procyshyn, 1995;Revett et al, 1997;Tsuji & Kaiser, 1991), NMR (Akerfeldt et al, 1996;Finn et al, 1992;Marsden et al, 1988;Shaw et al, 1991), #uorescence (Clark et al, 1993;Malik et al, 1987;Maurer et al, 1995), using a calcium mimic dye (Sharma et al, 1997) and using a calcium chelator (Linse et al, 1993). However, analysis of calcium-binding data from such model peptides is potentially complicated by the fact that EF-hand peptides have been shown to dimerize (Kay et al, 1991;Shaw et al, 1990Shaw et al, , 1992Shaw & Sykes, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of calcium-binding data from such model peptides is potentially complicated by the fact that EF-hand peptides have been shown to dimerize (Kay et al, 1991;Shaw et al, 1990Shaw et al, , 1992Shaw & Sykes, 1996). Attempts to quantitate the extent of dimerization in EF-hand peptides have utilized such techniques as sedimentation equilibrium (Kay et al, 1991;Maurer et al, 1995), NMR (Shaw et al, 1991), #uorescence (Maurer et al, 1995), and circular dichrosim (Monera et al, 1992). In addition to work on a full EFhand site, dimerization constants have been derived using NMR for isolated EF-hand loop regions of calmodulin site 3 (Wojcik et al, 1997).…”
Section: Introductionmentioning
confidence: 99%